A mixed-method approach to bankruptcy prediction: Altman z-score vs. Springate s-score - Agustina, Yumniati; Hilaludin, Hilaludin (International Journal of Applied Finance and Business Studies, 2024)
This study aims to determine the cause of the bankruptcy of PT. Cahyabintang Respati using the Almant Z-Score method and the Springate S-Score method and find out the differences between the two methods. This study uses primary company data obtained directly from CBR companies. The research method used is a mixed method (Mix Method), which is a qualitative and quantitative method. The final results of this study indicate that the main cause of the bankruptcy of PT. CBR that is continuing to decrease the fleet of ships owned by PT. CBR which results in a reduced drag of the ship and the company's revenue continues to experience a decline to the minus number and lead to bankruptcy. The calculation results of the Altman Z-score method of PT CBR's financial condition from 2007 to 2014 are still experiencing a healthy financial condition and in 2015 to 2018 the financial condition of PT. CBR experienced a gray condition (Gray Area) and in 2019 the financial condition of PT. CBR is in a bankruptcy position while the Springate method calculation results show that in 2007 to 2014 the financial condition of PT. CBR is still in a healthy financial condition, further from 2015 until 2019 PT. CBR is experiencing a difficult financial condition or based on bankruptcy. After testing the independent sample t test using the SPSS program, there was no significant difference between the Almant Z-Score and Springate methods in analyzing the bankruptcy of PT. CBR.